2023
DOI: 10.1093/infdis/jiad162
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Vaccination Among Patients Receiving Maintenance Renal Replacement Therapy: Immune Response, Real-World Effectiveness, and Implications for the Future

Abstract: Chronic kidney disease affects more than 800 million people worldwide and often progresses to end-stage renal disease, which requires maintenance dialysis. Patients receiving dialysis are at higher risk for severe respiratory infections, including SARS-CoV-2 (the causative agent of COVID-19). In addition, many patients who receive dialysis also receive immunosuppressive treatments for conditions such as systemic vasculitis, systemic lupus erythematosus, or malignancies. Many studies have shown that while mRNA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 54 publications
1
2
0
Order By: Relevance
“…The mean of anti-SARS-CoV-2 IgG class antibodies titers three to four weeks after the second vaccine dose was more than twice lower in hemodialysis patients as compared to controls in our study. Similarly, in other studies, patients undergoing dialysis exhibited lower antibody titers than the general population [20,21,[31][32][33]. The results of the study from Israel were similar to ours.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The mean of anti-SARS-CoV-2 IgG class antibodies titers three to four weeks after the second vaccine dose was more than twice lower in hemodialysis patients as compared to controls in our study. Similarly, in other studies, patients undergoing dialysis exhibited lower antibody titers than the general population [20,21,[31][32][33]. The results of the study from Israel were similar to ours.…”
Section: Discussionsupporting
confidence: 90%
“…Thus, the duration of dialysis treatment is important for the developing cellular immunity. The results of previous stud-ies [32,33,45,46] showed that the amount of anti-SARS-CoV-2 antibodies decreased rapidly a few months after vaccination in patients with kidney diseases. Our results are in line with these studies.…”
Section: Discussionmentioning
confidence: 96%
“…Recent studies have described antibody responses to fourth booster dose in people with CKD. 55 , 56 Understanding the serological and cellular responses in KTRs, dialysis and CKD population beyond the initial primary vaccine schedule (e.g. Doses 4 or more) is essential to inform schedule recommendations and clinical care.…”
Section: Discussionmentioning
confidence: 99%